Immunodepression in the surgical patient and increased susceptibility to infection - Volk, Hans-Dieter (BioMed Central, 2002)
Multiple organ failure is the major problem in intensive care patients. The failure of the organ 'immune system' is frequently overlooked, however. In this issue the article by Angele and Faist provides an excellent review of the topic. Deactivation of monocyte and lymphocyte functions seems to play a key role in post-traumatic immunodepression. To accompany that review we summarize our knowledge of the mechanisms of deactivation. Stress response, lipopolysaccharide translocalization and tissue injury contribute to 'immunoparalysis'. Recently developed, well standardized assays now allow us to monitor the immune system like other organ functions and opens new approaches for therapeutic interventions.